A heteroepitaxially grown two-dimensional metal–organic framework and its derivative for the electrocatalytic oxygen reduction reaction. Issue 19 (19th April 2022) - Huo, Meiling; Sun, Tu; Wang, Yanzhi; Sun, Pengfei; Dang, Jingshuang; Wang, Bin; Dharanipragada, N. V. R. Aditya; Inge, A. Ken; Zhang, Wei; Cao, Rui; Ma, Yanhang; Zheng, Haoquan
Abstract : Two-dimensional (2D) metal–organic frameworks (MOFs) have become a hot topic recently due to their high surface area, larger number of exposed active sites, and improved conductivity. Abstract : Two-dimensional (2D) metal–organic frameworks (MOFs) have become a hot topic recently due to their high surface area, larger number of exposed active sites, and improved conductivity. Combining different 2D MOFs could introduce new physical and chemical properties. Here, we have synthesized a heteroepitaxially grown 2D zeolitic imidazolate framework with a leaf-like morphology (ZIF-L). ZIF-L has a layer-by-layer dense structure, which possesses a high content of N and metal ions as active sites. ZIF-L-Co is heteroepitaxially grown on ZIF-L-Zn, while ZIF-L-Zn@ZIF-Co has been successfully prepared. After pyrolysis, the heteroepitaxially grown MOF derived ultra-small Co nanoparticle immobilized nitrogen doped carbon (NC) material (HM-Co@NC) exhibits superior oxygen reduction reaction (ORR) activity ( E onset = 0.998 V, E 1/2 = 0.905 V) and better stability than Pt/C, achieving well-qualified assemblies for use in rechargeable Zn–air batteries.